PERUBAHAN AGAMA MALIM Religious Change in Agama Malim - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
The agama Malim is that of nativistic and messianic Toba Batak religion closely associated with Si Singa Mangaraja's dynasty. Si Singa Mangaraja VII, the latest king of the Si Singa Mangaraja's dynasty, was the great Priest-King of the Batak. He was regarded as living manifestation of the deity. Some of the authors of Batak state that basically this ethnical religion creed is animist, with special reference to Si Singa Mangajara, together with several Muslim elements, although whether Si Singa Mangaraja XII was a Muslim is highly and politically debatable. The death of Si Singa Mangaraja XII in 1907 gave both the movement a nationalistic fillip resulting in the development of another movement called Parhudamdarn, which was based on the worship of Si Singa Mangaraja